Systematic feature analysis on timber defect images - Ummi Rabaah Hashim; Siti Zaiton Mohd Hashim; Azah Kamilah Muda; Kasturi Kanchymalay; Intan Ermahani Abd Jalil; Muhammad Hakim Othman (International Journal of Advances in Intelligent Informatics, 2017)
Feature extraction is unquestionably an important process in a pattern recognition system. A defined set of features makes the identification task more efficiently. This paper addresses the extraction and analysis of features based on statistical texture to characterize images of timber defects. A series of procedures including feature extraction and feature analysis was executed to construct an appropriate feature set that could significantly separate amongst defects and clear wood classes. The feature set aimed for later use in a timber defect detection system. For Accessing the discrimination capability of the features extracted, visual exploratory analysis and confirmatory statistical analysis were performed on defect and clear wood images of Meranti (Shorea spp.) timber species. Results from the analysis demonstrated that there was a significant distinction between defect classes and clear wood utilizing the proposed set of texture features.